Source Identification, Bioavailability, and Risk Assessment of Heavy Metals Pb, Cu, and Zn in Surface Sediments of Kelabat Bay, Bangka Island - Mohammad Agung Nugraha; Mu’alimah Hudatwi; Fajar Indah Puspita Puspita Sari (Marine Science Department Diponegoro University, 2019)
Although concentrations of many heavy metals has been measured totally, they may not give a good indicator for environmentally hazard to organism. The purpose of this study is to identify sources, determine bioavailability, and assess risk based on the geochemical fractionation of heavy metals Pb, Cu and Zn on the surface sediments of Kelabat Bay, Bangka Island. Fractionation of heavy metals was analyzed by sequential extraction. The concentrations of heavy metals Pb, Cu, and Zn in sediments ranged from 8.86-29.21 mg.kg-1 (average 16.85 mg /kg), 0.16-9.54 mg.kg-1 (average 4.39 mg.kg-1), and 25.58-237.24 mg.kg-1 (average 71.99 mg.kg-1). Pb and Zn in Kelabat Bay are more bound to non-residual fractions (F1+F2+F3) or non-resistant with a range of 60.63-89.87% and 47.98-84.66% that are mainly come from anthropogenic activities. Cu tend to be stored or bound to the residual fraction (F4) with a proportion of 97.7-100% meaning that it comes from natural sources. Based on the Risk Assessment Code (RAC), Pb have a low to moderate risk in the environment and Zn heavy metals are not at risk to low. These conditions indicate the potential for biological availability (bioavailability) of Pb and Zn in the inner bay waters. For heavy metals Cu is not at risk in the environment.